PENGARUH MEDIA PEMBELAJARAN PREZI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI SMP NEGERI 3 PADANG - DILLA HAIMI PUTRI, Drs. Suib Awrus, M.Pd., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2017)
This article aims to determine the effect of instructional media use Prezi to the learning outcomes of students in Arts in class VII SMP Negeri 3 Padang.The methodology of this research is quantitative method in this research is to design a method Quasi Exsperiments nonequivalent control group design. The sample selection study was conducted with a purposive sampling technique. Sampling criteria are the number of students at most incomplete, namely class VII.1 (Experiment) and VII.3. (Control). The instrument used is the achievement test. This type of instrument is objectively shaped test article with a double election a total of 20 questions.The results showed that there are differences in outcomes after the implementation of instructional media art Prezi in the material in class VII SMPN 3 Padang. Based on the hypothesis test carried out that the value of t = 8.210 and ttable = 2.000. This means that tcount> ttable, then Ho is rejected and H1 accepted. It can be concluded that the